2020
DOI: 10.1080/02670844.2020.1813517
|View full text |Cite
|
Sign up to set email alerts
|

Physical and photocatalytic properties of Nd codoped (Ag, Cu)TiO2 thin films

Abstract: Transparent co-doped TiO 2 thin films have been fabricated by sol-gel dip-coating. The doping is achieved using low concentrations of neodymium (Nd), silver (Ag), and copper (Cu). A significant effect of doping is noticed on the morphology and optical properties of thin films. XRD analysis confirms the formation of a pure anatase phase with a deterioration of the crystallinity upon doping. The co-doped TiO 2 thin films present larger crystallite size compared to other films. The surface roughness revealed by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…To overcome this instability, neodymium (Nd) has been added to some reaction systems. [12][13][14][15][16][17][18][19] It has been reported that when Nd was preloaded on the supports and then Ag was loaded on the Nd-supports, the surface areas of the supports increased and the stability of Ag on the surface was greatly improved. It is suggested that this is due to the creation of large roughness or pores on the supports, which prevent the Ag particles loaded on the support from moving at high temperature.…”
Section: Stabilization Of the Et Catalyst By Addition Of Ndmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this instability, neodymium (Nd) has been added to some reaction systems. [12][13][14][15][16][17][18][19] It has been reported that when Nd was preloaded on the supports and then Ag was loaded on the Nd-supports, the surface areas of the supports increased and the stability of Ag on the surface was greatly improved. It is suggested that this is due to the creation of large roughness or pores on the supports, which prevent the Ag particles loaded on the support from moving at high temperature.…”
Section: Stabilization Of the Et Catalyst By Addition Of Ndmentioning
confidence: 99%
“…Although the ET catalyst gave high NH 3 production activity, repeated experiments at 500-300 °C resulted in a significant decrease in activity. In an effort to stabilize the activity, we found that preloading Nd on the support (called the ND method [12][13][14][15][16][17][18][19] ) could stabilize the Ag/TiO 2 catalyst and achieve high activity. Finally, we investigated the reason why NH 3 can be generated in the presence of a large excess of oxygen and water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Specific detectivity is a very significant parameter which describes the performance of the photo-detector and its ability to detect the weak signal 96 . The detectivity for this device was calculated by using equation [97][98][99][100][101] :…”
Section: Electrical Properties Of Linbo 3 / Si and Ag Decorated Linbo...mentioning
confidence: 99%
“…The photocatalytic activity can be affected by numerous parameters such as the crystallographic structure, particle size, surface area, particle morphology, lattice defects and type of dopant elements. 23,39 Based on XRD analysis, the Nd-Y nanoparticles have the smallest particle size which can enhance the specific surface area of the nanomaterial. The higher the specific surface area, the higher the energy of the particles and the better the photocatalytic activity.…”
Section: The Photocatalytic Activitymentioning
confidence: 99%